Parallel assessment of globin lentiviral transfer in induced pluripotent stem cells and adult hematopoietic stem cells derived from the same transplanted β‐thalassemia patient. (4th October 2013) - Tubsuwan, Alisa; Abed, Soumeya; Deichmann, Annette; Kardel, Melanie D.; Bartholomä, Cynthia; Cheung, Alice; Negre, Olivier; Kadri, Zahra; Fucharoen, Suthat; von, Christof; Payen, Emmanuel; Chrétien, Stany; et al.
ABSTRACT A patient with βE/β0‐thalassemia major was converted to transfusion‐independence 4.5 years ago by lentiviral gene transfer in hematopoietic stem cells while showing a myeloid‐biased cell clone. Induced pluripotent stem cells (iPSCs) are a potential alternative source of hematopoietic stem cells. If fetal to adult globin class, switching does not occur in vivo in iPSC‐derived erythroid cells, β‐globin gene transfer would be unnecessary. To investigate both vector integration skewing and the potential use of iPSCs for the treatment of thalassemia, we derived iPSCs from the thalassemia gene therapy patient and compared iPSC‐derived hematopoietic cells to their natural isogenic somatic counterparts. In NSG immunodeficient mice, embryonic to fetal and a partial fetal to adult globin class switching were observed, indicating that the gene transfer is likely necessary for iPSC‐based therapy of the β‐hemoglobinopathies. Lentivector integration occurred in regions of low and high genotoxicity. Surprisingly, common integration sites (CIS) were identified across those iPSCs and cells retrieved from isogenic and nonisogenic gene therapy patients with β‐thalassemia and adrenoleukodystrophy, respectively. This suggests that CIS observed in the absence of overt tumorigenesis result from nonrandom lentiviral integration rather than oncogenic in vivo selection. These findings bring the use of iPSCs closer to practicality and further clarify our interpretation of genome‐wide lentivector integration. Stem Cells2013;31:1785‐1794